Feasibility of using sailfin catfish meal as an alternative to commercial fishmeal in the diets of juvenile guppy (Poecilia reticulata) - Raneesha de Fonseka; Kumudu Radampola (Journal of Fisheries, 2022)
A six weeks feeding trial was conducted to elucidate the effect of fishmeal produced from sailfin catfish (SCM) by replacing imported commercial fishmeal (FM) in the diet of Poecilia reticulata to reduce the cost of feed. Twenty one days old guppy fry (1.99±0.09 cm; 0.07±0.02 g) were fed four diets using different levels of SCM; control diet (CD; 0% SCM), 10SCM (10% SCM), 20SCM (20% SCM) and 30SCM (30% SCM). SCM contained higher protein content (69.5%) compared to FM (61%). Final body weight, %ADG, %SGR or FCR (1.77±0.16 – 2.21±0.26) and food consumption (9.3±0.1 – 9.45±0.5) did not influence by inclusion of SCM.  Survival (>80%) did not influence by the type and quantity of fishmeal inclusion. Moreover, significantly higher profit index for 30SCM (8.94±1.43) and 20SCM (7.88±4.23) was recorded than CD (5.17±4.43) which contained imported, expensive FM.  Overall, the present study revealed that commercial fishmeal can be fully replaced by SCM in the diets of juvenile guppy without any adverse effects on their growth. Therefore, producing fishmeal using sailfin catfish, which is an invasive species in reservoirs in Sri Lanka and an underutilized source, will be a feasible method to overcome the invasive problem.